The importance of parents in the neonatal intensive care units - Hercília Guimarães (Hygeia Press di Corridori Marinella, 2015)
The premature birth and the hospitalization in a neonatal intensive care unit (NICU) are potential risk factors for the development and behavior of the newborn, as has been shown in recent studies. Premature birth of an infant is a distressing event for the family. Several feelings are experienced by parents during hospitalization of their baby in the NICU. Feelings of guilt, rejection, stress and anxiety are common. Also the attachment processes have the potential to be disrupted or delayed as a result of the initial separation of the premature newborn and the mother after the admission to the NICU. Added to these difficulties, there is the distortion of infant's "ideal image", created by the family, in contrast with the real image of the preterm. This relationship-based family-centered approach, the Neonatal Individualized Developmental Care and Assessment Program (NIDCAP), promotes the idea that infants and their families are collaborators in developing an individualized program to maximize physical, mental, and emotional growth and health and to improve long-term outcomes for the high risk newborns. The presence of parents in NICUs and their involvement caring their babies, in a family centered care philosophy, is vital to improve the outcome of their infants and the relationships within each family.   Proceedings of the 11th International Workshop on Neonatology and Satellite Meetings · Cagliari (Italy) · October 26th-31st, 2015 · From the womb to the adult Guest Editors: Vassilios Fanos (Cagliari, Italy), Michele Mussap (Genoa, Italy), Antonio Del Vecchio (Bari, Italy), Bo Sun (Shanghai, China), Dorret I. Boomsma (Amsterdam, the Netherlands), Gavino Faa (Cagliari, Italy), Antonio Giordano (Philadelphia, USA)